2020
DOI: 10.1111/cts.12792
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects of Topical Omiganan in Patients With Mild to Moderate Atopic Dermatitis in a Randomized, Placebo‐Controlled, Phase II Trial

Abstract: Omiganan is an indolicidin analog with antimicrobial properties that could be beneficial for patients with atopic dermatitis. In this randomized, double‐blind, placebo‐controlled, phase II trial we explored the efficacy, pharmacodynamics, and safety of topical omiganan once daily in 36 patients with mild to moderate atomic dermatitis. Patients were randomized to apply topical omiganan 1%, omiganan 2.5%, or vehicle gel to one target lesion once daily for 28 consecutive days. Small but significant improvements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
16
2
Order By: Relevance
“… 69 , 70 Directly targeting S aureus is also an active area of investigation. These treatments include natural products with anti– S aureus activity, 71 synthetic antimicrobial peptides, 72 and S aureus lytic agents. 73 There is currently no approved S aureus vaccine.…”
Section: Potential Therapy In the Pipelinementioning
confidence: 99%
“… 69 , 70 Directly targeting S aureus is also an active area of investigation. These treatments include natural products with anti– S aureus activity, 71 synthetic antimicrobial peptides, 72 and S aureus lytic agents. 73 There is currently no approved S aureus vaccine.…”
Section: Potential Therapy In the Pipelinementioning
confidence: 99%
“…Dawgul et al showed a significant anti-staphylococcal and anti-biofilm effect of two amphibian AMPs (citropin 1.1 and temporin A) [164]. Furthermore, a phase II trial of omiganan, an indolicidin analog, revealed its potential for improving microbial dysbiosis on AD skin and a small, but significant effect on clinical scores encouraging further research on the implementation of AMPs [165].…”
Section: Therapeutic Methods With the Potential Of Restoring The Normal Skin Microbiotamentioning
confidence: 99%
“…Omiganan gel is an AMP with broad-spectrum activity against gram-positive and gram-negative bacteria and fungi. 29 In a 28-day, phase 2, RDBVCT in adults with mild-to-moderate AD, 2.5% omiganan led to significant improvements in SCORAD (SCORing atopic dermatitis), body surface area, morning itch, and dybiosis when compared with the vehicle. No local AEs were reported.…”
Section: Antimicrobial Agents: Amp and Topically Applied Commensal Organismsmentioning
confidence: 95%
“…No local AEs were reported. 29 Given the reduction in microbial diversity with AD flares and the recognized exacerbation of AD by S aureus, topical supplementation with commensal organisms that kill S aureus has been proposed as therapy. 13 Isolation of S hominis with antieS aureus activity, bacterial expansion, and application to lesional skin in adults with AD (targeted microbiome transplant) reduced S aureus within 24 hours of application.…”
Section: Antimicrobial Agents: Amp and Topically Applied Commensal Organismsmentioning
confidence: 99%